Transferrin receptors recycle to cis and middle as well as trans Golgi cisternae in Ig-secreting myeloma cells (The Rockefeller University Press, 1986)
The recycling itinerary of plasma membrane transferrin receptors (TFR) was charted in IgG-secreting mouse myeloma cells (RPC 5.4) by tagging surface receptors with either bound anti-transferrin receptor antibodies (anti-TFR) or Fab fragments thereof and determining the intracellular destinations of the tagged receptors by immunocytochemistry. By immunofluorescence, TFR tagged with either probe were seen to be rapidly internalized and translocated from the cell surface to the juxtanuclear (Golgi) region. When localized by immunoperoxidase procedures at the electron microscopic level, the anti- TFR-labeled receptors were detected in all cisternae (cis, middle, and trans) of the Golgi stacks as well as in endosomes and trans Golgi reticular elements. There was no difference in the routing of TFR tagged with monovalent Fab and those tagged with divalent IgG. Tagged receptors were detected in Golgi stacks of approximately 50% of the cells analyzed. The position of the labeled cisternae within a given stack was found to be quite variable with cis and middle cisternae more often labeled at 5 min and trans cisternae at 30 min of antibody uptake. The finding that recycling plasmalemmal TFR can visit all or most Golgi subcompartments raises the likely possibility that any Golgi- associated posttranslational modification can occur during recycling as well as during the initial biosynthesis of plasmalemma receptors and other membrane proteins.